The quantitative definition of N-vinylpyrrolidone and 2-methyl-5-vinylpyridine units ratio in the copolymers by UV-spectrophotometry - S. A. Kedik; D. V. Eremin; Yu. V. Kochkina; E. S. Zhavoronok; V. V. Suslov; A. V. Panov (Тонкие химические технологии)
The quantitative definition method of N-vinylpyrrolidone and 2-methyl-5-vinylpyridine ratio units in the copolymers using UV-spectrophotometry was developed. Copolymers were prepared by radical copolymerization using azo-bisisobutiric dinitrile as the initiator. On the basе of experimental results and simple mathematical transformations the simplified formula of calculation of the maintenance of 2-methyl-5-vinylpyridine units in the copolymer, including extinction coefficients of poly-2-methyl-5-vinylpyridine and a copolymer sample is concluded. The validity of the method as compared to 13С NMR was shown. According to results obtained by that method the synthesized copolymers are characterized by reproduceable characteristics, in particular the content of 2-methyl-5- vinylpyridine units was found 30-40 mol.%.